Jam v. International Finance Corp. (U.S. Sup. Ct.). (June 2019) - Perkins, Nancy; Pei, Sally
Abstract : On February 27, 2019, the U.S. Supreme Court issued an opinion in Jam v. International Finance Corp., a case of critical importance for international organizations. The question presented in Jam was whether U.S. law affords international organizations absolute immunity from suit in the United States, or whether international organizations instead are entitled to only the more limited or "restrictive" immunity that applies to foreign sovereigns under the Foreign Sovereign Immunities Act.